The Impact of Motivation and Organizational Citizenship behaviour on Employees' Performance - Akindipe, Oluwaleke Ebenezer; Fadun, Olajide Solomon (Acta Universitatis Danubius. Œconomica, 2023)
The concepts of motivation are essential for organizational managers to know as a motivated group of employees is essential for organizational success because they will participate entirely in their job to bring in a high level of profitability for the organization. Organizational citizenship behaviour (OCB), on the other hand, refers to anything that employees choose to do spontaneously and of their own accord, which often lies outside of their specified contractual obligations. The study's general objective is to investigate the effect of motivation and organizational citizenship behaviour on employees’ performance in an organization. The specific goal is to examine the relationship between employee motivation and organizational citizenship behaviour. The survey research design was used for this study. The study population comprises all the 16000 staff members of First Bank of Nigeria in Lagos, while the sample size is 390. The study used primary data by employing a structured questionnaire. Three hundred eighty-four questionnaires were retrieved and analyzed. Data collected were processed using the Statistical Package for social science students (SPSS), and the Chi-square test was used to test the hypothesis. The regression coefficient (β=0.757) of the equation shows that a unit change in Motivation and organizational citizenship will exert a positive effect on employees’ performance at the p-value of (0.000), which is less than the level of significance at the 0.05 level (2-tailed). The result demonstrates that intrinsic motivation influences motivation in an organization. It was recommended that Managers persuade employees to commit to organizational citizenship behavior by fostering an environment that demonstrates leadership qualities and a new attitude and that mediating factors should be considered to encourage motivated workers to exhibit organizational citizenship behavior (OCB).